Kondobuleng Traditional Theater as a Media for Awareness of Waste Problems for a Sustainable Future - Prusdianto Prusdianto; Muhamad Jazuli; Sofyan Salam; Agus Cahyono; Syakhruni Syakhruni (Universitas Negeri Semarang, 2022)
Abstrak. This study was based on the lack of skills of fourth graders SDN Proyonanggan 10 Batang. This study aimed to develop, access feasibility and effectiveness of m-learning melodika, and also to describe the results of psychomotor-learning using m-learning melodika in the fourth grade at SDN Proyonanggan 10 Batang. This type of study is reasearch and development (R&D) with ADDIE model. The sample in this study is 5 fourth grade students of SDN Proyonanggan 10 which represents the total population of 32 students. Data collection techniques were implemented with tests, observations, interviews, questionnaires, and ducumentation. Data analysis techniques includes product data analysis, normality test, t-test and n-gain test. Assesment by material expert and media expert of 96.47% and 100%. Teacher and student responses of 96% and 100%. T-test, sig value 0,00 < 0.05and t counts larger than t table which is 18.500 > 2.776. N-gain test amounts to 0.74 with high criteria. Conclution of this study is the media “M-Learning Melodika” that is worthy to use in both pianika playing materials and effective for improving the pianika playing skills of 4th grade students.